Construction Site : Taking Flight! - Rinker, Sherri Duskey; Ford, AG (San Francisco : Chronicle Books, 2023)
Six truck friends travel to the airport to build a new terminal, expanding the airport for both planes and travelers.
Keywords: Construction equipment -- Juvenile fiction; Airports -- Juvenile fiction; Stories in rhyme; Airplanes -- Specimens; Construction equipment -- Fiction; Airports -- Fiction; Stories in rhyme; Toy and movable books; Stories in rhyme; Toy and movable books; Picture books